MENGAJAR GRAMMAR DENGAN PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN KOMPETENSI BERBICARA DAN MENULIS - Erna Pujiasih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
This paper discusses about the teaching strategy in teaching grammar with board game of snake and ladder to increase the speaking and writing competence. More specifically, the paper presents how to teach use game can increase the speaking competence in learning English. Teaching grammar is one the challenging for teacher to make the students competence in speaking and writing. Teaching English by using media of board game (snake and ladder) is interesting to teaching speaking and writing. This activities make the students more understand and increasing the speaking and writing use future tense. This game is media that simple and amusing for the students. It can be found that from the observation, questioner and practicing writing and speaking in the learning English by using game of snake and ladder. From the data of questioner, it shows that all of student answer that media board game can improve the student’s competence in speaking and writing in understanding the grammar of future tense. It is found that the students get enjoy, interesting, learning by playing, effective, understanding, creative thinking and remember the material. Using game of snake and ladder to teach speaking and writing competence increase the students in speaking skill. This media is good and interesting for students to make the students fluent and understand the grammar. This media is not only simple but also give many advantages and effective in teaching English.